Internationalization Of Small And Medium Enterprises In Indonesia: Towards Integrative Policy Approach Of Competitiveness And Connectivity - Fifi Junita; yuniarti yuniarti; Intan Innayatun Soeparna; Resistensia Kesumawardhani (Yuridika, 2023)
The paper focuses on the policy analysis influencing the internationalization of small and medium sized enterprises (SMEs) engaged in cultural and creative industries (CCIs) in Indonesia. Three approaches of internationalization are explored in this study: the market knowledge approach, the network approach and the international entrepreneurship approach. This article attempts to figure out internationalization as a process starting from the creating of favorable preconditions to the strengthening stage based on the interrelationship among those approaches. The purpose of this article tries to combine the important dimensions proposed by each approach towards an integrative policy approach based on the concept of competitiveness and connectivity. The conceptual model of integrated policy in this study contributes to resolve inefficiency issue as the main gap in the existing strategic policy on SME internationalization in Indonesia; enhance integrative policy analysis literature and propose a more integrated strategic policy for promoting internationalization.